Web coding & development all-in-one - McFedries, Paul (John Wiley & Sons, Inc., 2024)
Web Coding & Development All-in-One For Dummies is a one-stop resource for would-be developers who need guidance on the languages and steps used to build websites and applications. Learn the coding ropes and expand your existing skillset with this easy-to-understand guide. In these complete mini-books, you'll walk through the basics of web development, structuring a page, building and processing web forms, and beyond. Learn how to build a website or create your very own app with the advice of web coding and development experts. This edition expands JavaScript and CSS coverage while providing new content on server-side coding and the development stack. This Dummies All-in-One is great for you if want to develop coding skills but don't have a programming background. It's also perfect for professionals looking to brush up on their web development skills and get up to date on the latest trends and standards.
Includes index
Keywords: Web sites -- Design; Web site development; Sites Web; Conception; Sites Web; Développement